A Survey Report on Risk-aware Role-based Access Control Model (International Journal of Engineering and Computer Science, 2017)
Cloud computing is an advanced emerging technology that uses internet to provide reliable, convenient, on-demand services to customers. One of the interesting and most challenging area in cloud computing is access control model. MAC, DAC, RBAC, etc are traditional access control methods which controls the access to services and resources. Role based access control (RBAC) allows access based on role(s) assigned to a particular object, which increases security. There exist some risks like insider threats in RBAC. Risk-aware role based access control (RAAC) provides a mechanism that can manage the access to resources using two approaches of RAAC: traditional approach and quantified approach.